Health Literacy - Jordan, Tina L.; Aubrey, Harold L.; Stevenson, Andre P. (Groupwork, 2013)
Recent research literature indicates that African Americans (AA) generally execute advance directives to a much lower degree than do non-Hispanic Euro-American adults. The purpose of this research study was to investigate the degree to which social and demographic variables are associated with knowledge of advance directives among AA aging prisoners. A combined sample (N=100) of AA Aging Prisoners generated from three randomly selected sub-samples were collected from three of five state correctional facilities in a Mid-Atlantic Region in the United States. Each prisoner completed the Jordan Advance Directive Measurement Scale©. Three categorical groups emerged from the combined sample. Those groups were based on the Health Status question regarding knowledge of advance directives Null hypotheses were tested and data were analyzed using Pearson’s Chi-Square Test of Independence. There was no significant degree of independence between any of the three pairs of sub-groups. The researchers informally discovered the prisoners’ lack of basic knowledge of advance directives.